The white blood cell count (WBC) and neutrophil-to-lymphocyte ratio (NRL) in multiple sclerosis - R. Ya. Vivchar; V. M. Akimova; L. Ye. Lapovets; N. Ye. Lapovets (Kazimierz Wielki University, 2020)
Introduction. Multiple sclerosis (MS) is one of the main chronic inflammatory diseases of the central nervous system that causes functional disability in people. Assessment of the state of the immune system begins with an analysis of the total number of blood leukocytes and their population composition (the number of neutrophils and lymphocytes). The ratio of neutrophils and lymphocytes (NRL) is a marker of inflammation. The aim of the study. The aim of this study was to investigate the WBC and neutrophil-to-lymphocyte ratio in patients with different forms of MS.   Results. In patients with MS in 23.5% of cases the WBC is higher than 9×109/L. In 5.9% of МS cases leukopenia is observed, and in the vast majority of cases (70, 6%) the level of blood leukocytes was in the range of 4-9×109/L. Leukopenia and leukocytosis are more common in women than in men (p<0.05). Leukocytosis and leukopenia are most often found in RRMS form, while in the SPMS form patients in 93.8 % of cases the normal level of leukocytes found. MS's patients had a significantly higher NLR (p < 0.05) than the control group. No significant difference in WBC and NLR was found between groups of MS clinical forms. No association was found between NLR and an age and sex. Conclusions. NRL is an inexpensive and affordable indicator, which is determined by the automatic determination of the total number of leukocytes in the blood. It can be an additional informative indicator of inflammation against the background of normal leukocyte levels.